Tingkat Pengetahuan Petugas Rekam Medis Tentang Sensus Harian Rawat Inap di Rumah Sakit Santa Elisabeth Medan - Urim Gabriel Dinasti Laowo; Scere Sophia Sitorus (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Inpatient Daily Census (SHRI) is an activity of disability or counting of inpatients carried out daily in an inpatient room in order to find out the number of services provided to patients for 24 hours. The daily census of patients is carried out every day. This is so that the hospital can find out how many patients visit each day. The population used is all medical record officers at Santa Elisabeth Hospital Medan with a sample of 12 people. This type of research is descriptive research. The instruments used are interviews and observations. Descriptive data analysis. The results obtained that medical record officers with good knowledge (51.2%) and less (26.4%) it can be concluded that the level of knowledge of a medical record officer is influenced by the level of education received by each officer in order to create better performance and results. in patient care. It is recommended to hospitals to improve the quality of human resources, provide motivation, make plans for human resource needs based on the workload of medical recorders.